2021
DOI: 10.1108/jkm-06-2021-0486
|View full text |Cite
|
Sign up to set email alerts
|

Organisational agility, environmental knowledge and green product success

Abstract: Purpose The purpose of this study is to analyse the effect of organisational agility on environmental knowledge as an instrument for the successful development of eco-innovation in products. Design/methodology/approach This study used a cross-sectional design to collect data on the study variables from a sample of 184 Spanish manufacturing organisations. Structural equations with partial least squares were used to test the hypotheses. Findings Organisational agility is significantly linked to internal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 144 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…Different studies show the linkage between OA and GDC (Baškarada and Koronios, 2018;Rabal-Conesa et al, 2021;Arora et al, 2020). A study by Rabal-Conesa et al (2021) showed a…”
Section: Green Dynamic Capabilitymentioning
confidence: 99%
“…Different studies show the linkage between OA and GDC (Baškarada and Koronios, 2018;Rabal-Conesa et al, 2021;Arora et al, 2020). A study by Rabal-Conesa et al (2021) showed a…”
Section: Green Dynamic Capabilitymentioning
confidence: 99%
“…When enterprises invest in R&D, they not only create new knowledge, but also improve their absorptive capacity (Cohen and Levinthal, 1990). The improvement of absorptive capacity helps enterprises to acquire external knowledge and carry out environmental innovation (Rabal-Conesa et al, 2022). The combination of external knowledge acquisition and internal R&D can enable enterprises to effectively carry out internal R&D activities and benefit from knowledge complementarity (Lokshin et al, 2008).…”
Section: The Impact Of Iurc On Eementioning
confidence: 99%
“…Developing technologies to reduce environmental pollution is an expensive, complex, and highly uncertain task (Oke, 2013;Rabal-Conesa et al, 2022). Usually, it is difficult for enterprises to deal with the pressure of controlling environmental pollution only through internal research and development (R&D) (Chang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that knowledge acquisition lead toward ecological innovation (Chen et al , 2015; Lin and Chen, 2017; Pham et al , 2019; Shahzad et al , 2020) and that the success of the environmental innovation process depends on access to internal and external sources of knowledge (Ben Arfi et al , 2018; Rabal-Conesa et al , 2022). However, this line of research is still recent and more studies are needed to delve into the effect of knowledge management process on green innovation (Ben Arfi et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%